Does Good Knowledge On Dietary Risk Factors For Diabetes Translate Into Good Dietary Practice? Findings From A Suburban Community In Tampin, Negeri Sembilan - Nizam Baharom; Mohd Dzulkhairi Mohd Rani; Nadeeya Mohamad Nor; Nuurain Amirah Mohd Razi; Muhammad Arsyad Rohim; Wan Mohd Salman Wan Sallam; Wan Aina Mardhiah Wan Kamaruzaman; Shahzanani Shakirah Mohd Rifaie; Nazmi Aizuddin Adnan; Zairina A. Rahman (Malaysian Medical Association, 2024)
Non-Indexed Publication